Cobalt-doped Ba2In2O5 brownmillerites: an efficient electrocatalyst for oxygen reduction in alkaline medium - Jijil, C. P.; Patil, I. M.; Kakade, B.; Nandini Devi, R. (ACS omega, 2018)
A series of compounds with cobalt doping in the indium site of Ba2In2O5 brownmillerites exhibited excellent oxygen reduction activity under alkaline conditions. Doping (25%) retains the brownmillerite structure with disorder in the O3 site in the two-dimensional alternate layer along the ab plane. Further substitution of cobalt in the indium site leads to the loss of a brownmillerite structure, and the compound attains a perovskite structure. Cobalt-doped samples exhibited far better oxygen reduction reaction (ORR) activity when compared to the parent Ba2In2O5 brownmillerite. Among the series of compounds, BaIn0.25Co0.75O3−δ with the highest Co doping and oxygen vacancies randomly distributed in the lattice exhibited the best ORR activity. BaIn0.25Co0.75O3−δ showed a 40 mV positive shift in the onset potential with better limiting current density and a nearly four-electron-transfer reduction pathway when compared to the parent Ba2In2O5 brownmillerite.